Free COVID-19 Training Plan (2020)
To help out and contribute to the triathlon community in any small way we can, we have created a free training plan (completely free, no email sign-up required) that you can use during the current pandemic when swimming is not an option for most. Of course, different countries have implemented different measures to tackle the crisis, so it's impossible to cater for every single scenario. This plan assumes that you can ride (indoors will do just fine) and run (again indoors will do just fine if you have a treadmill and are not allowed to run outside). The plan is delivered through Training Peaks and available in three different versions, based on how much you typically train (7/12/17-hours-per-week-plan). Pick the one that most closely resemble your typical volume.